La vulgarisation de la géomorphologie glaciaire méditerranéenne. L'exemple du Matese (Apennin méridional, Italie) - Bruno Comentale (Physio-Géo)
Matese area is a rainy Mediterranean mountain whose highest peaks were glaciated during the last Pleistocene, above 1600 m a.s.l. Although of low extension, this typical glacial relief is to be popularized. In such a geomorphological popularization, glacial morphology is described, and limit conditions of spreading and discrepancy of glaciers are discussed. This allows to think about a presentation of the glacial phenomenon in a pedagogical way.